Americanism as a global idolatry of market and its impact on universities - Ostasiewicz, Walenty (Amerykanizm jako globalne bałwochwalstwo i jego wpływ na uniwersytety, 2020)
The main aim of this paper are critical reflections about the subservience of the academic elite (and ordinary scholars) to corporations, which is manifested by performing research and publishing papers, and fosters predatory politics of corporations. It is high time to wake up and open our eyes, and see that the so-called corporate social responsibility is in fact a social irresponsibility, that viatical insurance is a cynical mode for profiting from terminally ill persons, that customers are human beings who have dignity rather than monetary value and they cannot be packaged into portfolios. Everything relating to the stock exchange (interest rate, bonds, investments, instruments ) is a kind of pure speculation, and has nothing to do with the very production needed to ensure our livelihood, instead it serves to make the rich richer and the poor poorer. The primary aim of this paper is first of all to point to the existing extensive non-mainstream literature revealing the causes of this evil
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2020, Nr 18 (24), s. 43-97